Occurrence and Altitude of the Long‐Lived Nonspecular Meteor Trails During Meteor Showers at High Latitudes. Issue 8 (2nd August 2020) - Kozlovsky, A.; Lukianova, R.; Lester, M.
Abstract: Meteoroids entering the Earth's atmosphere produce ionized trails, which are detectable by radio sounding. Cylindrical underdense (and partly overdense) trails form a great majority of meteor echoes received by meteor radars (MRs). Additionally, the long‐lived nonspecular (LLNS) meteor echoes are received from irregularities of ionization generated along tracks of relatively large meteoroids. At high latitudes where the magnetic field is nearly perpendicular to the Earth's surface the LLNS echoes are possible only from non‐field‐aligned irregularities. The occurrence and height distributions of LLNS echoes are studied using MR observations at the high‐latitude Sodankylä Geophysical Observatory (SGO, 67°22′N, 26°38′E, Finland) during 2008–2019. Two parameters are analyzed: the percentage and height distribution of LLNS echoes. These LLNS echoes constitute about 3% of all MR detections. However, during certain meteor showers (i.e., the Geminids, Perseids, Quadrantids, Arietids or/and Daytime ζ‐Perseids, and Lyrids) the percentage of LLNS echoes is noticeably higher (about 10%, 8%, 7%, 7%, and 4%, respectively). Typically, the LLNSs occur ∼1–2 km higher than other echoes (in June–July the height difference is reduced to ∼0.5–1 km). Moreover, during the Lyrids, η‐Aquariids, Perseids, Orionids, and Leonids the LLNS echoes occur noticeably, up to 3–5 km, higher than the echoes from other types of trails. Plain Language Summary: Meteoroids entering the Earth's atmosphere produce the ionized trails, which are detectable by radars. Majority of such radar detections are the echoes from cylindrical ionized trails, which occur if the radar beam is perpendicular to the trail; that is, the reflection is specular. Typically, such echoes last less than one second. However, sometimes meteor radars observe unusually long‐lived meteor echoes and these echoes are nonspecular (LLNS echoes). At high latitudes where magnetic field is nearly perpendicular to the Earth's surface the LLNS echoes are possible only from non‐field‐aligned irregularities. The LLNS echoes are received from trails of bright meteors, and it is believed that key role in their generation belongs to the aerosol particles arising due to fragmentation and burning of large meteoroids. We found that usually about 3% of all meteor radar detections are LLNS echoes; however, during peaks of some meteor showers (Geminids, Perseids, Quadrantids, Arietids or/and Daytime ζ‐Perseids, and Lyrids) the percentage is larger, up to 7–10%. On average, the LLNS echoes occur ∼2 km higher than other echoes, and even higher (up to 3–5 km) during Lyrids, η‐Aquariids, Perseids, Orionids, and Leonids. These meteor showers are identified in the height distributions and/or occurrence of LLNS trails. Key Points: Long‐lived nonspecular echoes from non‐field‐aligned irregularities constitute 3% of all meteor radar detections Long‐lived nonspecular echoes from non‐field‐aligned irregularities occur few kilometers higher than other echoes During major meteor showers percentage or/and height of nonspecular echoes increase